Testing et certification - Claire Tardieu (Recherches en didactique des langues et des cultures, 2013)
Within the theme "Learning Languages differently", this paper focuses on the issue of language certification at the very moment when the means of assessment tend to evolve and different European and international certificates are superseding national diplomas. We will deal especially with two certificates which are seemingly incompatible : the Certificat de Compétence en Langues de l’Enseignement Supérieur (Cles) (The Language Certificate of Higher Education) and the C-Test (a specific type of cloze test).